Evaluation of Antipyretic Activity of Siddha Herbomineral Formulation - Surangusa Parpam (International Journal of Ayurveda and Pharma Research, 2023)
The aim of the present study was to assess the antipyretic activity of Siddha herbo-mineral formulation Surangusa Parpam at the dose level of 15mg/kg and 35mg/kg body weight, orally, in brewer yeast induced fever model Wistar rats. Fever was induced by subcutaneous injection of 10ml/kg of 20% w/v aqueous suspension of brewer’s yeast into the nape of the rat's neck. After eighteen hours feverish animals were treated with Surangusa Parpam 15mg/kg and 35mg/kg body weight, orally, and rectal temperatures were evaluated at 0, 1, 2 and 3 hours post-treatment by inserting a well-lubricated bulb of the clinical thermometer. Surangusa Parpam showed a significant decrease in the elevated body temperature of rats that remained sustained throughout the tested time points from 1 to 3 hours in the used model. 35mg/kg body weight dose level showed significant inhibition of elevated body temperature when compared with the standard control. These results indicate that the Antipyretic activity of Surangusa Parpam and in addition to its well-established anti-inflammatory activity possesses significant antihistamine activity that may be beneficial in symptomatic relief when it is used in the therapy of allergic and inflammatory disorders.